Ekstrak Teh Hijau Mengurangi Luas Area Fibrosis Paru Tikus - Desdiani; Iris Rengganis; Samsuridjal Djauzi; Agus Setiyono; Mohammad Sadikin; Sri Widia A. Jusman; Nurjati Chairani Siregar; Suradi; Putri C. Eyanoer (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundPulmonary fibrosis is often found in infectious diseases and chemical exposure in the work environment. Antifibrotic effects can befibropreventive and fibrolysis. Bleomycin can cause inflammation and pulmonary fibrosis. Catechin is proven can repair liverdamages due to alcohol induction. The aim of this study is to examine the effect of antifibrotic green tea catechin on reducing thearea of rat lung fibrotic.MethodsThis research was carried out in vivo experimentally in the Laboratory Animal Management Unit at Faculty of Veterinary MedicineIPB in 4 groups of rat experiments, consisting of 3 rats in the negative control group, 3 rats in the positive control group, 3 rats in thegroup of rats given bleomycin on the 8th day and 28thwith green tea extract every day from day 0 to 49 days (fibropreventive), 3groups of rats given bleomycin days 0 and 21 with green tea extract every day from day 15 to 49 (fibrolysis). Histopathologicalexamination was performe for all groups of rats.ResultsThis study showed that administration of green tea extract in fibropreventive groups and fibrolysis groups could reduce the fibrosisarea in rat lungs based on Aschroft's modified scale.ConclusionBased on the results of this study it was found that the anti-fibrotic activity of green tea extract was proven to be able to suppressthe development of pulmonary fibrosis both by fibropreventive and fibrolysis